Dynamics of a Caste Movement : the Rajbansis of North Bengal, 1910-1947 - Basu, Swaraj (New Delhi : Manohar, 2003)
With reference to Bengal, India.
Includes bibliographical references (p. [141]-148) and index.
Keywords: Rajbangsi (South Asian people) -- Politics and government -- 20th century; Bengal (India) -- Politics and government -- 20th century; India--Bengal -- Politics and government